Coal and waste direct liquefaction, using glycerol, polyethylene waste and waste tyres pyrolysis oil. Optimisation of liquids yield by response surface methodology. (10th May 2020) - Pinto, Filomena; Hidalgo-Herrador, José M.; Paradela, Filipe; Costa, Paula; André, Rui; Fratczak, Jakub; Snape, Colin; Anděl, Lukaš; Kusy, Jaroslav
Abstract: Coal and waste direct liquefaction was carried out to decrease the hydrocarbons production negative bearing to environment. The wastes studied were glycerol, polyethylene waste and waste tyres pyrolysis oil. Glycerol and waste tyres pyrolysis oil were blended with tetralin and used as solvent for coal direct liquefaction (T = 350–450 °C; N2 ; waste:tetralin at different weight ratios). Glycerol may be considered as a waste from the production of fatty acid methyl esters (FAME). Waste tyres pyrolysis oil showed to be a good hydrogen donor solvent. Solid polyethylene wastes were mixed with coal and used in coal co-liquefaction tests, which showed to be a good option to produce liquid hydrocarbons for fuels or raw materials for chemical industry. Although liquids yield using waste tyres pyrolysis oil or glycerol were high, respectively 62% wt. and 51% wt., the use of polyethylene allowed increasing them to 80% wt. Different experimental conditions were studied, namely: experimental temperature, run time, solvent type and composition and hydrogen initial pressure. The effect of commercial catalysts on co-liquefaction was also studied and the results obtained were compared with those obtained with coal impregnated with Fe or Mo (1% wt./coal). Response surface methodology (RSM) was used to predict the influence of the main experimental conditions studied on product yields. This methodology resulted to be a good one to predict coal liquefaction and co-liquefaction products yields, as predicted values were similar to experimental data. In addition, RSM approach led to the selection of tetralin as solvent and to the use of coal impregnated with 1% of Mo, as liquids yield increased up to 96% wt. Highlights: Coal liquefaction improvement by the use of glycerol, polyethylene and waste tyres pyrolysis oil. Waste tyres pyrolysis oil showed to be a good H donor solvent. Improvement of co-liquefaction by using impregnated coal with metals mixed with PE wastes. Optimisation of liquids production by Response Surface Methodology (RSM). The use of tetralin in co-liquefaction of PE wastes and coal impregnated with 1% of Mo led to liquids yield up to 96% wt.